Teknologi Pengolahan Pakan Ternak di Kabupaten Madiun Menuju Kawasan Pengelolaan Lingkungan Berkelanjutan - Rosyidah, Afifah; Amalia, Inka; Shomadany, Sholahus; Dwi, Indah Trisnawati; Shofiyah, Rohimatush (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The sustainability of livestock quality is greatly influenced by animal feed. Precision livestock feed products are very important for improving product quality and safety, improving the health and welfare of livestock, as well as reducing the environmental impact of livestock manure by processing it into natural organic fertilizer using a symbiotic mutualism technique between the animal husbandry and agriculture sectors. It is important for farmers to know how to ferment livestock waste to increase soil fertility. This process breaks down the organic materials in livestock manure into nutrients. This is necessary so that the nutrients are more stable and easily absorbed by plants; kills a number of parasites, bad bacteria and pathogens that can inhibit the plant growth process. For this reason, the livestock manure fermentation process is carried out correctly so that the results are optimal. With this fermentation method, plants show excellent growth and development and have superior quality when compared to plants without treatment. On the other hand, the Silage method is very suitable for stabilizing animal feed stocks. Farmers can make feed without having to look for grass every day, which still maintains its nutritional quality and the results show that almost all livestock like silage or this form of fermented feed.